Integration of LC-HRMS-Based Metabolomics, INS-1 Cell Assays, and Molecular Docking to Elucidate the Synergistic Antidiabetic Mechanism of the Kunyit–Asam Herbal Formulation - Muhammad Nurul Fadel; Emma Jayanti Besan; Nur Masyithah Zamruddin; Cut Intan Annisa Puteri; Nina Irmayanti Harahap (CV. Get Press Indonesia, 2025)
Diabetes mellitus remains a major global health burden, leading to growing interest in herbal formulations as complementary antidiabetic therapies. This study aimed to elucidate the synergistic antidiabetic mechanism of the traditional Kunyit–Asam herbal formulation by integrating LC-HRMS-based metabolomics, in vitro INS-1 pancreatic β-cell assays, and molecular docking analysis. Metabolomic profiling using LC-HRMS identified a diverse array of bioactive secondary metabolites, predominantly phenolic acids, flavonoids, and curcuminoids, which are associated with antidiabetic and antioxidant activities. Functional evaluation in INS-1 cells demonstrated that the Kunyit–Asam extract significantly enhanced glucose-stimulated insulin secretion (GSIS) and improved β-cell viability, indicating insulinotropic and cytoprotective effects. Furthermore, molecular docking analysis revealed that several identified metabolites exhibited strong binding affinities toward key diabetes-related molecular targets, including α-glucosidase, α-amylase, AMP-activated protein kinase (AMPK), insulin receptor substrate-1 (IRS-1), phosphoinositide 3-kinase (PI3K), and GLUT4 regulatory proteins. Integration of metabolomic, biological, and in silico findings suggests that the antidiabetic activity of Kunyit–Asam is mediated through multi-target modulation of insulin signaling pathways, inhibition of postprandial glucose-regulating enzymes, and protection against oxidative stress. These results support a synergistic pharmacological mechanism driven by multiple phytoconstituents rather than a single dominant compound. This study provides scientific evidence supporting the traditional use of Kunyit–Asam as an antidiabetic herbal formulation and offers valuable insights for future herbal-based drug development.